(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Extracts of leaves and stems of Chlorophytum borivilianum were subjected to preliminary phytochemical screening and in-vitro antimicrobial studies. The results of the preliminary investigation revealed the presence of alkaloids, glycosides, steroidal nucleus, saponins and tannins in both parts. The methanolic extract of leaf and stems part were investigated for antimicrobial activity using agar disc diffusion method. Six clinical strains of human pathogenic microorganisms, comprising 3 Gram +ve, 1 Gram -ve and 2 fungi were utilized in the studies. The leaf extract of Chlorophytum borivilianum displayed overwhelming concentration dependent antimicrobial properties, inhibiting the growth of Staphylococcus aureus and Bacillus cereus, far above that of ampicillin used in a concentration of 1.0 g/ml. The extract was less sensitive to 2 Gram -ve bacteria in the assay. In antifungal assay, the growth of Aspergillus niger and Candida albicans, were inhibited in the same manner comparable to voriconazole the reference drug used in the study. The methanol extract of stem also displayed a concentration related antibacterial activity, inhibiting the growth of S. aureus comparable to ampicillin at 1.0 g/ml. The extract was least active against Escherichia coli with a mild activity at 1.0 g/ml. The extract exhibited weak activities against C. albicans as well as A. niger. Both plant parts seem to justify their ethno medical uses.